Managing Innovation in Highly Restrictive Environments Lessons from Latin America and Emerging Markets - Cortés-Robles, Guillermo; García-Alcaraz, Jorge Luis; Alor-Hernández, Giner (Management and Industrial Engineering,, 2019)
This book presents the integration of new tools, the modification of existing tools, and the combination of different tools and approaches to create new technical resources for assisting the innovation process. It describes the efforts deployed for assisting the transformation of Product-Services Systems and explains the main key success factors or drivers for success of each tool or approach applied to solve an innovation problems. The book presents a set of case studies to illustrate the application of several tools and approaches, mainly in developing countries. .